A new species of the fungus-farming ant genus Mycetagroicus Brandão & Mayhé-Nunes (Hymenoptera, Formicidae, Attini) - Brandão,Carlos Roberto Ferreira (2008)
The fungus-farming ant genus Mycetagroicus Brandão & Mayhé-Nunes was proposed based on three species from the Brazilian "Cerrado": M. cerradensis, M. triangularis and M. urbanus. Here we describe a new species of Attini ant of the genus Mycetagroicus, M. inflatus n. sp., based on two workers collected in eastern Pará State, Brazil. A new key for species identification, comments on differences among species and new geographical distribution data are furnished.